Visual Environment Factors Influencing Staying Behaviors During Cycling on Countryside Greenways - Ting WEN; Yun ZHANG; Ming DU (Fengjing Yuanlin)
ObjectiveCountryside greenways represent an organic extension of urban green slow-moving traffic systems into suburban areas, addressing urban residents' demands for closer contact with nature and fostering the development of an integrated urban-rural belt. Cycling, as a slow-moving activity that combines outdoor recreation and leisure tourism, constitutes one of the primary modes of activity on countryside greenways. Compared to urban greenways, cycling on countryside greenways is characterized by faster speeds, longer distances, and longer durations, causing cyclists to pay closer attention to the amenities, scenery, and safety aspects of the staying spaces when selecting a site and determining the duration of their sojourn. Since visual perception accounts for 80%-90% of the information humans receive from their environment, it exerts a profound influence on human behavior and environmental experiences. Riders on countryside greenways are often attracted to the distinctive visual environments and tend to make spontaneous stops, which could increase safety risks. Furthermore, existing regulatory frameworks have not sufficiently addressed the safety concerns of cycling on countryside greenways, resulting in insufficient attention to this issue. Therefore, investigating the characteristics of staying behaviors and the influencing factors of the visual environment on countryside greenway cycling holds practical significance and expands upon existing greenway research. The planning and design of staying points in conjunction with the visual environment not only help improve the safety and user-friendliness of greenway cycling but also leverage scenic resources to entice cyclists to linger longer, thereby enhancing the usage intensity of the countryside greenway and further promoting the development of the rural tourism economy.MethodsThis research focuses on the Qingshan Lake Greenway in Hangzhou. This greenway, spanning across urban built-up areas, rural settlements, and natural scenic zones, showcases a unique combination of lakeside and mountainous landscapes, making it a representative example of countryside greenways. Through field research and analysis of cycling trajectory data, local staying spaces are categorized into nodes and road sections. Four key indicators — number of stays, duration of stays, frequency of stays, and staying rate — are established to provide a comprehensive understanding of user engagement and interaction with the greenway environment. This approach allows for a more nuanced analysis of how cyclists utilize and experience the greenway spaces. Additionally, visual environmental features are analyzed through image semantic segmentation and ArcGIS, with a view to exploring their impact on staying behaviors during cycling. Correlation and multiple regression analyses are employed to determine the intensity of the visual environment’s influence on staying behaviors.ResultsThe findings reveal that cyclists tend to stay longer at nodes compared to road sections. However, the overall staying time remains brief, averaging less than one minute. This indicates low utilization rates of greenway stations and viewing platforms. Conversely, the frequency of spontaneous stays on road sections is higher, suggesting that cyclists are more inclined to make impromptu stays during their rides. Given the prevalence of cycling accidents on countryside greenways, these spontaneous stays may pose significant safety risks. Moreover, the visual environment’s influence varies between nodes and road sections; staying behaviors at nodes are primarily affected by the visual field area, while those on road sections are influenced by green visibility, with higher greenery levels promoting impromptu short stays.ConclusionThis research endeavors to develop spatial strategies for enhancing the staying behaviors of cyclists on countryside greenways, with a view to improving the usage intensity of greenway nodes and ensuring the safety of road segment traversal. Particular emphasis is placed on the optimization of staying spaces situated in poor visual environments, because the visibility of prominent landscape features, such as water bodies and mountain vistas, has been found to exert a significant influence on cyclists' propensity to linger. At the node level, strategies should focus on broadening the visual field and prolonging the duration of stays. This can be achieved through strategic optimization of plant layouts and reduction of physical obstructions, which collectively serve to enhance the perceivability of the surrounding natural scenery. In contrast, the spatial design of road segment staying spaces must prioritize safety considerations, especially in areas constrained by adjacent mountains or cliffs. By expanding the width of select road sections and introducing cantilevered structures or recessed micro-terraces along them, the creation of small yet safe “pocket” staying spaces can provide cyclists with suitable rest areas without compromising the overall flow of traffic. This, in turn, contributes to a more vibrant and active greenway network.The systematic integration of the spatio-temporal distribution patterns of cyclists' staying behaviors with the influencing factors of the visual environment laid the foundation for this research, which not only informs the enhancement of greenway station usage intensity and cycling safety, but also provides a robust methodological framework for the optimization of small and micro staying point placement along road segments. Looking ahead, further investigations incorporating other greenway usage characteristics, such as cycling distances and incident-prone locations, could shed additional light on the construction of cyclist-friendly countryside greenway environments that cater to the diverse needs and behavioral patterns of users.